(untitled) (Experimental biology, 2015)
Known conserving media for the keeping of botany objects (including the media elaborated by authors and protected by invention documents of Kazakhstan Republic) from the position of keeping of plant objects for the botany laboratory lessons, including the opportunities of the quick making of micro-preparations from fixing plants were considered. Authors’ experience of laboratory lessons showed that clearing activity displayed the media with glycerin or soluble sugars with optical activity in their compositions. From ready everyday means for the keeping and clarity of botany objects the clear fair shampoos were recommended. For the clarity and softening of rug plant objects their exposition in 30-40% carbamide (urine amide) solution during several hour, with the possibility of long-term objects’ keeping in this liquid without indicators of destruction was recommended.